Claiming Quality: Discourses on Quality and Arts Education in Sri Lanka - Prabha, S. A.; Manuratne, M. (Faculty of Arts University of Jaffna, Sri Lanka, 2022)
Discourses on quality are central to how the corporatization of the State university system has occurred in Sri Lanka. Neoliberal universities maintain an extensive governance system that implements quality through a disciplinary system that aims to produce quality within the university. In this paper, I examine how such disciplinary measures are also productive. They produce discourses on quality that are then performatively enabled by the university community. I particularly focus on how Arts faculties navigate such discourses on quality by examining how policy documents, guidelines, self-evaluation reports, annual reports, and even promotion circulars perform a productive role, leading the university community to produce the practices that are demanded of them. I will specifically focus on IR guidelines, SLQF, annual reports and SERs produced by the UGC and the University of Kelaniya as well as publicly available data on academics from the two Arts Faculties at the University of Kelaniya. In this paper, I focus on the Manual for Institutional Review in my analysis.
Keywords: Quality; Corporatization; Neoliberalism; State universities; Governance system